Macromodel-based simulation of membrane action in reinforced concrete structural members. Issue 3 (3rd April 2021) - Yousefi, Behrooz; Esfahani, Mohammad Reza; Tavakkolizadeh, Mohammadreza
Abstract: This paper is devoted to present a two-stage fiber element-based method for studying the membrane action of RC structural members. The proposed method combines small and large displacement formulations through two separate stages. These stages include compressive arch action in small displacements and catenary stage in large displacements, separately. For structural problems with both geometric and material nonlinearity, the total Lagrangian and the updated Lagrangian formulations are taken into account to derive the governing equations. Also, the suggested method is able to consider the bond-slip behavior of reinforcing bars and shear deformations in the structural members. Finally, the accuracy of the authors' method is compared with the available experimental results and previous analytical methods in the literature. The results show that such a modeling method is capable of simulating compressive arch stage concurrently with the catenary action behavior.